Biological Activity of Some Malaysian Plant Extracts - Sukari, Mohd Aspollah; Takahashi, Shozo (1988)
Extracts obtained from three Malaysian Labiatae plants, including Ocimum sanctum, Mentha arvensis and Orthoshiophon staminea, were investigated for their biological activity. The volatile fraction of each plant was isolated and the major components were characterized by gas chromatography (GC), gas chromatography-mass spectrometry (GC-MS), and nuclear magnetic resonance (NMR). The antibacterial and antifungal activity, insecticidal activity and inhibition of the germination of seeds of the volatile fraction and residue were studied.